Agent Based Adaptive Discussion Room (ABADR): A Collaborative Adaptive Direct Discussion Tool for Open University System - N.A.M Jabari; M Hariadi (Pusat Teknologi Instrumentasi dan Otomasi (PTIO) - Institut Teknologi Bandung, 2010)
Through this research a study has been introduced for adaptive education at the Open University. Through reviewing a number of systems available in this field ABAH system have been selected as a system built basically on the AHA! Adaptive system which provides both adaptive presentation as well as navigation, to solve the problem of the direct discussion among the students and the teacher which is not supported by AHA! or any other system. A proposal is introduced as an adaptive discussion tool with customized interface presenting guidance for the student to defining the appropriate students to discuss with by arranging the students in the discussion list and give them different colors. This proposal is mainly based on 3 agents: 1) chat user model agent, 2) chat adaptive agent, and 3) chat monitoring agent, beside adaptation rules knowledge base which will provide rules to construct adaptation strategy. Keywords: ABADR, Collaborative Adaptive, Open University System, AHA!